HYPOGLYCEMIC ACTIVITY OF ETHANOLIC LEAF EXTRACT OF MIMUSOPS ELENGI LINN IN STREPTOZOTOCIN INDUCED DIABETIC RATS - S. K. JAFFAR; S. M. KHASIM; M. GURU PRASAD; MD. IBRAHIM (The Bioscan, 2011)
The ethanolic extract of Mimusops elengi Linn. (Sapotaceae) leaf was used for its anti hyper glycemic effects in wistor albino rats. Diabetes was induced in albino rats by administration of single doses of streptozotocin (STZ) 40mg/kg body weight, i.p. The ethanolic extract M. elengi at optimum dose concentration of 100mg/kg body weight was administered as a single dose/day to diabetes induced rats for a period of 30 days. The effect of leaf extract on blood glucose, insulin (in plasma), hemoglobin, glycosylated haemoglobin (HbA1c) and carbohydrate metabolic enzymes such as glucokinase, glucose -6-phospate dehydrogenase and glycogen content in liver and kidney, and gluconeogenic enzymes such as glucose -6 phosphatase, fructose 2,6 bis phosphatase levels has also been studied. Leaf extract elicit significant (p<0.05) reduction of blood glucose levels and lipid profile levels in liver and kidney of diabetic rats except HDL, and carbohydrate metabolic enzymes significantly (p<0.05) increased. The extract also caused significant (p<0.05) increases in plasma insulin levels, increased total proteins, albumin, globulin and A/G ratio. A significantly (p<0.05) decrease in gluconeogenic enzymes in liver and kidney was observed.